(untitled) (Baghdad Science Journal, 2021)
Light is an important factor that influences the growth and photosynthetic efficiency of microalgae; however, little is known about how light intensity together with the wavelength affect the photosynthetic capacity and growth of marine microalgae. In the present study, the growth of the marine green microalga Dunaliella parva was studied and optimized under different light intensities (25 70 μmol m-2 s-1) and qualities (blue, green, and red) in comparison with white light at 40 μmol m-2 s-1 as a control. The growth was monitored by counting the cell number, pigment content, Chl a, Chl b, and carotenoids concentrations. The optimal growth and highest photosynthetic efficiency (Fv/Fm) were recorded at a light intensity of 40 μ mol m-2 s-1, white light, and 1.25 M NaCl (1.47 and 0.678×106 cell mL-1, respectively). The activity of antioxidant enzymes, including catalase and peroxidase, as well as ascorbate content, showed the highest values of 0.190 µM/min.mg Chl, 0.434 and 13.3 mg/g f.wt. respectively, under the green light, which confirmed the presence of environmental stresses.